Sub‐10 nm Radiolabeled Barium Sulfate Nanoparticles as Carriers for Theranostic Applications and Targeted Alpha Therapy - Reissig, Falco (ChemistryOpen, 2020)
Invited for this month's cover is the group of Kristof Zarschler at the University of Dresden, Germany. Read the full text of their Full Paper at 10.1002/open.202000126.